The many nationalities of Hristofor Žefarović - Gjorgјiev, Vancho; Sarakinski, Vojislav (Universitatea „Ovidius” din Constanța, 2019)
Less than a century after the death of Hristofor Žefarović (1690– 1753), a renowned artist, author, merchant, heraldist and supporter of the “Illyrian idea”, Balkan historiographies began trying to determine his ethnicity – or, rather, his nationality – under the influence of national ideologies for which they sought legitimacy. However, the question of the attested identity markers of Hristofor Žefarović presents a complex methodological problem that cannot (and should not) be treated unilaterally, on the basis of fragmentary and selective pieces of information brought out of context. A thorough analysis of the extant sources, containing an extensive set of contextual identity markers, shows that – at this time, and until a better and more explicit source comes to light – modern historiography is objectively unable to determine the ethnicity of Hristofor Žefarović in modern terms. Furthermore, it is questionable whether this kind of conclusion can be reached at all, as our sources testify to a remarkable fluidity in ethnical markers and norms of self-determination in the times of Žefarović, which would be nearly outrageous under the terms of modern-day politics. Consequently, from a methodological viewpoint, the case of the ethnicity and self-identification of Hristofor Žefarović cannot be defined in any other way, except as putting the past in function of building contemporary national ideologies.
Keywords: Hristofor Žefarović, Ottoman Macedonia, ethnicity, identity markers, self-identification